Beasts of Eden : walking whales, dawn horses, and other enigmas of mammal evolution - Wallace, David Rains, 1945- (University of California Press, 2004)
Mammals first evolved at about the same time as dinosaurs, and their story is perhaps the more fascinating of the two--in part because it is also our own story. In this literate and entertaining book, eminent naturalist David Rains Wallace brings the saga of ancient mammals to a general audience for the first time.